Transcatheter Mitral Valve Replacement in Failed Bioprosthetic Valve, Ring, and Mitral Annular Calcification Associated Mitral Valve Disease Using Balloon Expandable Transcatheter Heart Valve - Hiroki A. Ueyama; Patrick T. Gleason; Vasilis C. Babaliaros; Adam B. Greenbaum (Methodist DeBakey Cardiovascular Journal)
Transcatheter mitral valve replacement (TMVR) using the SAPIEN platform has been performed in failed bioprosthetic valves (valve-in-valve), surgical annuloplasty rings (valve-in-ring), and native valves with mitral annular calcification (MAC) (valve-in-MAC). Experience over the past decade has identified important challenges and solutions to improve clinical outcomes. In this review, we discuss the indication, trend in utilization, unique challenges, procedural planning, and clinical outcomes of valve-in-valve, valve-in-ring, and valve-in-MAC TMVR.